STUDENTS BARRIERS IN TOEFL TEST A STUDY AT ENGLISH DEPARTMENT STUDENTS OF UNIVERSITAS PGRI SUMATERA BARAT - Supiyati; Rika Afriyanti; Herfyna Asty (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
This study aims to identify the barriers faced by students at PGRI University of West Sumatra in completing the TOEFL test, particularly in the three main skills: listening comprehension, structure and written expression, and reading comprehension. This study uses a mixed methods approach combining quantitative and qualitative methodologies. The research instruments consist of questionnaires and interviews distributed to selected students using purposive sampling techniques. Quantitative data were analyzed by calculating percentages, while qualitative data were analyzed through data reduction, data presentation, and conclusion drawing. The results of the study indicate that students experience significant barriers in all three aspects of TOEFL skills. In listening, the main challenges include limited vocabulary, barriers understanding fast conversations, and the intonation of native speakers. In structure and written expression, students faced barriers in understanding complex grammar rules and the use of academic vocabulary. In reading comprehension, the dominant barriers lay in understanding main ideas, inferences, and texts with complex structures. These findings confirm that students' challenges are not limited to a single skill but encompass all aspects of academic English proficiency.